Facial recognition system used in verification Systems for library users - Botez, Andra-Manuela; Volovici, Rodica; Volovici, Daniel; Repanovici, Angela (Qualitative and Quantitative Methods in Libraries, 2019)
Most of the literatures that deal with library security take into account the security of collections, buildings, or equipment. The security of the libraries is an important concern for library staff. There are security systems for collections, but in the context of terrorism, we are interested that people who have access inside the library to be in good faith. Checking the library card is the key to enter the library. It is non-transferable. We present a complementary system of the entrance permit through the facial recognition of users, developed and tested in a public library as collaboration between two Romanian universities: Transilvania University of Braşov, Lucian Blaga University of Sibiu and Brasov Public Library.